Uji validitas dan reliabilitas instrumen kuesioner gambaran penggunaan obat nyeri haid secara mandiri pada mahasiswi Fakultas Kedokteran Universitas Mataram - Rosa Ninty Oktamadila; Iman Surya Pratama; Ni Made Amelia Ratnata Dewi (Universitas Mataram, 2022)
Self-medication often becomes a choice for various complaints, one of which is menstrual pain. Regarding the description of the use of menstrual pain medication independently, it is still limited. The use of a questionnaire as a research instrument that has been tested for validity and reliability is very necessary. Therefore, this study aims to develop and test the validity and reliability of the description of the independent use of menstrual pain medication in female students. This research is a descriptive survey type with a cross-sectional design. The validity test was carried out using a qualitative and quantitative professional assessment method, namely by using the Content Validity Ratio (CVR). An advance validity test was conducted by 5 experts and 40 respondents. The reliability test was carried out with 40 respondents and used the Chronbach Alpha value. The results of the validity test obtained 28 questions with a CVR value of 1. Facial validity was declared valid after one repair. The reliability of the test obtained Cronbach's Alpha coefficient value of 0.934. Based on the validity and reliability test of the questionnaire, it was declared valid and reliable so that all questions could be used as an instrument to find out the description of the use of menstrual pain medication independently.